Potential Islamic Finance as an Alternative for UMKM Scale, Instrument Development and Validation in Indonesia - Ayu Anita Novanka; Evi Devi Nurkarimah; Farida Aryani; Susan Cholidiyah (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2024)
This study examines the potential of Islamic finance as an alternative financing channel for Micro, Small, and Medium Enterprises (UMKM) in Indonesia, addressing a persistent gap in empirically validated measurement instruments for this purpose. A purpose-built 21-item scale, designated the Potential Islamic Finance as an Alternative for UMKM Scale (PIFAUS), was developed and administered to 420 UMKM operators across five provinces on the island of Java through a structured face-to-face survey. Exploratory factor analysis revealed a six-dimensional structure accounting for approximately 76.29% of total variance, with the six factors identified as Personal Religious and Social Values, Sectoral Appropriateness, Financing Schemes and Opportunities, Accessibility, Cost Competitiveness, and Ease of Financing Access. Confirmatory factor analysis conducted within a PLS-SEM framework confirmed the model's construct validity, with multiple goodness-of-fit indices meeting either perfect or acceptable threshold criteria. The Cronbach's Alpha coefficient of 0.843 confirmed the high internal reliability of the instrument. Findings indicate that religious and social values constitute the most influential dimension driving UMKM orientation toward Islamic finance, while cost competitiveness and ease of financing access remain underdeveloped relative to the sector's stated positioning. The PIFAUS instrument offers both a theoretical contribution to the Islamic finance measurement literature and a practical diagnostic tool for policymakers, financial regulators at the Otoritas Jasa Keuangan (OJK), and institutional stakeholders seeking to expand Islamic finance penetration within Indonesia's UMKM economy.